Effect of Topical Brimonidine 0.15% on Conjunctival Injection after Strabismus Surgery in Children - Dong Hyun Kim; Hee Kyung Yang; Sang Beom Han; Jeong-Min Hwang (Journal of Ophthalmology)
Purpose. To investigate the effects of topical brimonidine 0.15% instillation on conjunctival injection after strabismus surgery in children. Methods. We retrospectively analyzed 63 Korean children who underwent strabismus surgery for intermittent exotropia. Patients received topical brimonidine 0.15% after surgery for up to 4 weeks. Conjunctival injection was objectively assessed using a software that automatically scored the region of interest from the image of the bulbar conjunctiva. Conjunctival injection scores were compared with those of the control group who were not prescribed topical brimonidine. Results. The mean scores of conjunctival injection after rectus muscle recession and resection were significantly lower in the brimonidine group than the controls at 4 weeks after surgery (P=0.008  and  0.046, respectively). There was no significant difference in intraocular pressure between the two groups. No adverse effects, such as dry mouth, fatigue/drowsiness, headache, sedation, hypotension, or bradycardia, were reported. Conclusions. Administration of topical brimonidine 0.15% after strabismus surgery is efficacious and safe in reducing postoperative conjunctival injection.